Intraganglionic reactive oxygen species mediate inflammatory pain and hyperalgesia through TRPA1 in the rat - Zhang, Youping; Asgar, Jamila; Shou, Huizhong; Pak, Joshua; Da Silva, Joyce Teixeira; Ro, Jin Y. (Frontiers in Pain Research, 2023)
Reactive oxygen species (ROS) are generated in nociceptive pathways in response to inflammation and injury. ROS are accumulated within the sensory ganglia following peripheral inflammation, but the functional role of intraganlionic ROS in inflammatory pain is not clearly understood. The aims of this study were to investigate whether peripheral inflammation leads to prolonged ROS accumulation within the trigeminal ganglia (TG), whether intraganglionic ROS mediate pain hypersensitivity via activation of TRPA1, and whether TRPA1 expression is upregulated in TG during inflammatory conditions by ROS. We demonstrated that peripheral inflammation causes excess ROS production within TG during the period when inflammatory mechanical hyperalgesia is most prominent. Additionally, scavenging intraganglionic ROS attenuated inflammatory mechanical hyperalgesia and a pharmacological blockade of TRPA1 localized within TG also mitigated inflammatory mechanical hyperalgesia. Interestingly, exogenous administration of ROS into TG elicited mechanical hyperalgesia and spontaneous pain-like responses via TRPA1, and intraganglionic ROS induced TRPA1 upregulation in TG. These results collectively suggest that ROS accumulation in TG during peripheral inflammation contributes to pain and hyperalgesia in a TRPA1 dependent manner, and that ROS further exacerbate pathological pain responses by upregulating TRPA1 expression. Therefore, any conditions that exacerbate ROS accumulation within somatic sensory ganglia can aggravate pain responses and treatments reducing ganglionic ROS may help alleviate inflammatory pain.